The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.2217/14796708.3.2.153
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic potential of statins in multiple sclerosis: immune modulation, neuroprotection and neurorepair

Abstract: Statins as inhibitors of 3-hydroxy-3-methyl glutaryl coenzyme A reductase are widely used as cholesterol-lowering drugs. Recent studies provide evidence that the anti-inflammatory activity of statins, which is independent of their cholesterol-lowering effects, may have potential therapeutic implications for neuroinflammatory diseases such as multiple sclerosis (MS), Alzheimer's disease and brain tumors, as well as traumatic spinal cord and brain injuries. Studies with animal models of MS suggest that, in addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 106 publications
0
23
0
Order By: Relevance
“…Current MS treatment is only partially effective, however, and it is important to identify existing or novel classes of drugs that may benefit MS therapy. Recent studies have demonstrated that oral cholesterol-lowering HMG-CoA reductase inhibitors (known as statins) have immunomodulatory properties (Ghittoni et al 2006;Markovic-Plese et al 2008). In experimental autoimmune encephalomyelitis (EAE), a model of MS, and in vitro, statins have been shown to promote the differentiation and expansion of myelin protein-reactive regulatory Th2 cells and to suppress the upregulation of MHC class II and co-stimulatory molecules on APCs (Neuhaus et al 2002;Youssef et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Current MS treatment is only partially effective, however, and it is important to identify existing or novel classes of drugs that may benefit MS therapy. Recent studies have demonstrated that oral cholesterol-lowering HMG-CoA reductase inhibitors (known as statins) have immunomodulatory properties (Ghittoni et al 2006;Markovic-Plese et al 2008). In experimental autoimmune encephalomyelitis (EAE), a model of MS, and in vitro, statins have been shown to promote the differentiation and expansion of myelin protein-reactive regulatory Th2 cells and to suppress the upregulation of MHC class II and co-stimulatory molecules on APCs (Neuhaus et al 2002;Youssef et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Statins are orally administered competitive inhibitors of 3-hydroxy-3-methyl-glutaryl-coenzyme A (HMG-CoA) reductase, an enzyme that catalyzes the conversion of HMG-CoA to mevalonic acid (MA) (8). As effective cholesterol-lowering agents, statins have been extensively used for prevention of cardiovascular disease.…”
mentioning
confidence: 99%
“…These oxygen radicals further aggravate tissue damage (10,24,42). Glutamate-mediated calcium toxicity induced mitochondrial dysfunction and the associated loss of energy supply together with formation of free oxygen radicals are important targets of spinal cord injury studies (36). These radicals react with the cellular lipids and mitochondrial membranes and produce lipid peroxides.…”
Section: █ Discussionmentioning
confidence: 99%
“…They are used for treatment of dyslipidemias and prevention of cardiovascular diseases (15,45). On last two decades, extensive research has focused on these agents, revealing their neuroprotective and immunomodulatory effects (15,29,36,45,50).…”
Section: █ Introductionmentioning
confidence: 99%
See 1 more Smart Citation